Review of Maria Zarimis', Darwin’s Footprint: Cultural Perspectives on Evolution in Greece (1880-1930s) - Trubeta, Sevasti (Historein, 2017)
Maria Zarimis. Darwin’s Footprint: Cultural Perspectives on Evolution in Greece (1880-1930s). Budapest & New York: CEU Press, 2015. 340 pp.